Necrobiosis Lipoidica through the Microscope - Parul Mehrotra; Rajalakshmi Tirumalae (Journal of Dermatology and Dermatologic Surgery, 2024)
Background: Necrobiosis lipoidica (NL) is a rare, idiopathic granulomatous dermatitis, known for its strong association with diabetes mellitus (DM). Most of the literature available is based on the western population, and studies focusing on histopathology are few. The largest series from India reported so far comprised six cases. Purpose: The objective of this study was to highlight the histopathologic spectrum and presentations of NL in Indian patients. Methods: We reviewed eight cases diagnosed as NL over 10 years. Clinical features were recorded, and various histopathologic parameters were reassessed. Results: The age ranged from 26 to 77 years with a mean of 42, with a female preponderance of 3:1. Clinical presentations included erythematous indurated plaques, painful nodules, and ulcers on the legs. Only one patient had DM. Provisional diagnosis ranged from granuloma annulare to mycosis fungoides. One patient had generalized involvement, with nodules on the upper limbs, trunk, and face. His DM was detected after the onset of lesions. Histopathologic features common to all cases were altered collagen, tiered arrangement of necrobiosis, myointimal hyperplasia and luminal narrowing of blood vessels, and perivascular lymphohistiocytic infiltrate. The upper dermis was involved in five cases and subcutis in four cases. The patterns of granulomas were mixed (6/8), tuberculoid (1/8), and palisading (1/8). Plasma cells were predominant in only one case. Perineural inflammation was seen in one case. A perforating variant was seen in one case. None of the cases had dermal mucin. Conclusion: Diagnosis of NL relies on clinicopathologic correlation. Our series highlights variations in histopathology compared to classically described findings such as involvement of upper dermis, striking vascular changes, rarity of palisading granulomas, perineural inflammation, and paucity of plasma cells. It is important to be aware of these in order to avoid misdiagnosis.